Socioeconomic Context, Parenting, and Childhood Antisocial Outcomes - Williams, Corrie (My University, 2014)
This study explored the relationships between level of advantage, parent perceptions of social support and cohesion, parental monitoring, and childhood antisocial behaviour. The sample consisted of 4008 participants (M = 2037, F = 1971), sourced from The Longitudinal Study of Australian Children (n=10090). Structural equation modelling and tests of moderation and mediation were performed to analyse a path model and t-tests examined between group differences. The results of these analyses indicated that the lower the advantage the higher the antisocial behaviour. High disadvantage correlated with low social cohesion and low social support. Parental monitoring mediated the direct effects of social support and social cohesion on antisocial behaviour. However, there were no differences found between advantaged and disadvantaged contexts in the level of parental monitoring. Further, it was shown that support moderates the relationships between disadvantage and social cohesion, parental monitoring, and subsequent antisocial behaviour. The results of this research highlight the complex and interrelated nature of socioeconomic context, parenting, and childhood antisocial behaviour outcomes. The use of these variables in future research may progress the consolidation of developmental sources of risk, provide a clearer understanding of antisocial behaviour outcomes, and provide better targeted macro-level intervention.
Keywords: Child Development -- Behaviour; Families -- Socio-economic status; Families -- Parents and Parenting; Disadvantage; Families and relationships; Childhood and child development; Families; Disadvantage; Child Development; Parents and Parenting; Socio-economic status; Behaviour; Childhood and child development; Families and relationships